Fatty acids linked to cardiovascular mortality are associated with risk factors - Sven O. E. Ebbesson; Venkata S. Voruganti; Paul B. Higgins; Richard R. Fabsitz; Lars O. Ebbesson; Sandra Laston; William S. Harris; John Kennish; Benjamin D. Umans; Hong Wang; Richard B. Devereux; Peter M. Okin; et al. (International Journal of Circumpolar Health, 2015)
Background: Although saturated fatty acids (FAs) have been linked to cardiovascular mortality, it is not clear whether this outcome is attributable solely to their effects on low-density lipoprotein cholesterol (LDL-C) or whether other risk factors are also associated with FAs. The Western Alaskan Native population, with its rapidly changing lifestyles, shift in diet from unsaturated to saturated fatty acids and dramatic increase in cardiovascular disease (CVD), presents an opportunity to elucidate any associations between specific FAs and known CVD risk factors. Objective: We tested the hypothesis that the specific FAs previously identified as related to CVD mortality are also associated with individual CVD risk factors. Methods: In this community-based, cross-sectional study, relative proportions of FAs in plasma and red blood cell membranes were compared with CVD risk factors in a sample of 758 men and women aged ≥35 years. Linear regression analyses were used to analyze relations between specific FAs and CVD risk factors (LDL-C, high-density lipoprotein cholesterol, triglycerides, C-reactive protein, systolic blood pressure, diastolic blood pressure, heart rate, body mass index, fasting glucose and fasting insulin, 2-hour glucose and 2-hour insulin). Results: The specific saturated FAs previously identified as related to CVD mortality, the palmitic and myristic acids, were adversely associated with most CVD risk factors, whereas unsaturated linoleic acid (18:2n-6) and the marine n-3 FAs were not associated or were beneficially associated with CVD risk factors. Conclusions: The results suggest that CVD risk factors are more extensively affected by individual FAs than hitherto recognized, and that risk for CVD, MI and stroke can be reduced by reducing the intake of palmitate, myristic acid and simple carbohydrates and improved by greater intake of linoleic acid and marine n-3 FAs.